ANALISIS PERAN ALOKASI DANA DESA DALAM MENDORONG PERTUMBUHAN EKONOMI LOKAL - SUMANJAYADI, SUMANJAYADI; PUTRA, SANDI JUSTITIA (GANEC SWARA, 2024)
This study aims to analyze the management of Village Fund Allocation (ADD) in Menggala Village and identify factors that influence the process, both supporting and inhibiting. By using a descriptive method, this study describes the phenomenon of ADD management systematically and objectively, without testing or controlling variables. The results of the study are expected to provide valuable input for the village government in improving the effectiveness of ADD management for the welfare of the community. This study adopts the theory of Community-Based Development (CBD) and Participatory Budgeting (PB), which emphasizes the importance of community participation in the planning and management of ADD through Musrenbangdes. In addition, this study also shows the role of social capital and adaptive governance, which facilitate mutual cooperation and flexibility in managing development projects. The use of digital technology in financial reporting and the implementation of multi-layered governance and e-government support transparency and accountability. Overall, this study concludes that the application of participatory and transparent principles in ADD management contributes to increasing the effectiveness of village development. This approach not only strengthens public trust but also increases community involvement, creating more inclusive and sustainable development in Menggala Village.